Factors Affecting Technical Efficiency of Trawl Fishery in Penang, Malaysia - Lim, Ghee Thean (2011)
The main objective of this study is to investigate the level of technical efficiency and factors affecting technical inefficiency for a sample of local trawl vessel operating in Penang, Malaysia. This study was conducted due to the declining trend of marine fish landing of Penang trawl fishery 1993 – 2009. The annual cumulative number of days of local trawl vessels in these seventeen years was also declining in tandem. Data of this study were collected through questionnaire survey that was conducted from November 2009 to January 2010. Sixty-nine fishermen were selected randomly for this study. Information on landing per trip, number of crew, fishing days per trip, diesel consume per trip, gross registered tonnage of vessel and horsepower of vessel were gathered and analyzed by using two approaches namely, stochastic frontier analysis (SFA) and data envelopment analysis (DEA). Furthermore, the determinants of technical inefficiency (family background, age, years of experience and education level of fishermen together with age of vessel and possession of echo sounder) were analyzed through SFA and tobit regression. The results from both approaches (DEA and SFA) indicated that technical efficiencies among vessels varied between 12.3% and 100%. The mean technical efficiency for DEA approach was 56.6% while SFA approach recorded 71.7%. The inefficiency model from SFA indicated that experience of fishermen, age of vessels and possession of echo sounder contributed positive influences on technical efficiency. In addition, the inefficiency model from tobit regression showed that family background, education, experience of fishermen and possession of echo sounder contributed positive influences on technical efficiency. The inefficiency models from both SFA and tobit regression consistently indicated that possession of echo sounder was the only significant variable having positive influence on technical efficiency which meant a vessel with possession of echo sounder would be more efficient compared with those vessels without echo sounder. Hence, this study suggested that fishermen should be encouraged to acquire an echo sounder and improve the marine fish landings through offering loans, subsidies or other incentives provided by the government to lessen the high capital investment cost borne by the fishermen.